PUBLIC RELATIONS COMMUNICATION STRATEGY PT. ANTAM IN LOBBY AND NEGOTIATION - Lena Wijaya; Dini Safitri (Jurnal Komunikasi dan Bisnis, 2022)
In everyday communication without us realizing it, there are circumstances that require us to campaign and negotiate with others. The most important thing that a Public Relations must prepare when he wants to lobby and negotiate is that he must first read who the target lobby is and know the techniques in lobbying and negotiating are the objectives of this research by looking at the communication strategies used by the Public Relations of PT. ANTAM in lobbying and negotiating. This research approach uses descriptive qualitative. The data collected is based on in-depth interviews or in-depth interviews involving relevant informants. Based on interviews with informants in this study, it can be seen that the lobbying and negotiation techniques used by Public Relations at PT. ANTAM in the face of distrust from the public from negative news so that the program that is being carried out can be carried out again as before, namely mitigation. As for the communication strategy used, the media used to disseminate information and programs that are being run by PT Antam are, by using mainstream mass media such as print media and television media and then through public service announcements, to convey information, persuade and educate the public with the aim of to build the company's brand image so that the problems faced by Antam can be resolved without creating new problems.